2013
DOI: 10.1021/ja4055367
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Symmetry on Single-Molecule Conductance

Abstract: We have measured the single-molecule conductance of a family of bithiophene derivatives terminated with methyl sulfide gold-binding linkers using a scanning tunneling microscope based break-junction technique. We find a broad distribution in the single-molecule conductance of bithiophene compared with that of a methyl sulfide terminated biphenyl. Using a combination of experiments and calculations, we show that this increased breadth in the conductance distribution is explained by the difference in 5-fold symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
71
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 20 publications
11
71
1
1
Order By: Relevance
“…LUMO) can be attributed to charge transfer. It is interesting to note that a recent experimental investigation by Campos et al [34] on the impact of molecular symmetry on single molecule conductance also corroborate this observation. They have found that reduced symmetry of bithiophene restricts the inter-ring torsion rotations when confined in a junction.…”
Section: Resultssupporting
confidence: 61%
“…LUMO) can be attributed to charge transfer. It is interesting to note that a recent experimental investigation by Campos et al [34] on the impact of molecular symmetry on single molecule conductance also corroborate this observation. They have found that reduced symmetry of bithiophene restricts the inter-ring torsion rotations when confined in a junction.…”
Section: Resultssupporting
confidence: 61%
“…Recently, we reported that the 5-fold symmetry of thiophene results in wider conductance histograms than those of biphenyl due to higher rotational barriers when bound in the break junction. 44 Extending the study to higher oligomers of thiophene (1−6 units long), we also found that the 4-unit molecule (T4) unexpectedly shows a higher peak conductance value than its 3-unit counterpart (T3), as seen in Figure 3. 43 This is because the two central thiophene rings of T4 can rotate to planarize without significantly altering the junction length, in contrast to T3, which can get locked in a non-planar, less conductive, conformation.…”
Section: Relating Transport To Molecular Structuresupporting
confidence: 51%
“…42 As the planarity of a molecule increases, conjugation is enhanced, and conductance increases ( Figure 2B); a similar effect is seen in the conductance of bithiophenes. 44 This mirrors how the twisting between neighboring π systems in a conjugated polymer greatly reduces the transfer integral between them and hinders intrachain transport. Recently, we reported that the 5-fold symmetry of thiophene results in wider conductance histograms than those of biphenyl due to higher rotational barriers when bound in the break junction.…”
Section: Relating Transport To Molecular Structurementioning
confidence: 85%
“…3b). The relatively narrow breadth of the conductance histogram peaks is indicative of a rather rigid backbone in this class of molecules 28,33 . A 2D histogram for TDO3 that retains the displacement information and is created from the same data (Fig.…”
Section: Resultsmentioning
confidence: 99%